Research on advanced support and deformation control technology of a high-geostress soft rock tunnel - Peng, Tao; Liu, Pengrong; Shi, Ming; He, Fanmin; Wang, Weijia; Wang, Anmin; Yan, Tao (Frontiers in Earth Science, 2025)
IntroductionA reasonable advanced support system is crucial for ensuring stable excavation in tunnels with weak surrounding rock. This study aims to address the problems of instability, large deformation, and prolonged construction period in the sidewalls of tunnel faces in plateau high-geostress carbonaceous slate tunnels in western mountainous areas.MethodsBased on lithology analysis and creep tests, we propose enhanced over-head pre-support, rapid initial support closure, and increased steel arch stiffness. The proposed approach was validated via numerical modeling and field tests.ResultsResults show that compared to no forepoling (Case I), Cases II–V reduced deformation by 17%, 21%, 44%, and 46%, respectively. The additional arch over-support improves stability and reduces sidewall deformation. The combined "arch-wall over-support + HW175 steel arch + 6m anchors" system shortened initial support formation from 20 to 12 days.DiscussionThese findings support the design of active-passive support systems for high-stress weak rock tunnels and offer insights for similar projects.